Fronts of biocapitalist exploitation: The labor not protected by law through the example of the production of science and cognitive labor at the Public University - Baron de Vargas, Tuany (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2021)
The university environment is the protagonist of a development strategy, since it is an environment of technological and human production, of intersecting subjectivities, with potential for the source of human emancipation through the exercise of work. In this sense, becomes a new value currency of a new capitalism, which reconfigures the models of labor exploitation and subjectivity. It is situated in the center of gravity of a biocapitalism. The present work seeks to analyze this issue through the specificity of the Brazilian University and the forms of work established in it as a producer of science and technology.